Knowledge and Preventive Behaviour Regarding Diarrheagenic Escherichia Coli Infection Amongst Final-Year Medical Students in Universitas Sumatera Utara - Eklesia, Maryori; Simatupang, Maria Magdalena (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Background: Escherichia coli, a gram-negative facultative anaerobe bacterium is one of the most important etiologies of acute diarrhea, still a serious public health problem and cause of morbidity and mortality in infants, children, the elderly, and people with immune deficiency. The source of contamination is through the consumption of contaminated food, improperly processed dairy and agricultural products, and contact with people who have poor hygiene. The purpose of the study is to determine the level of knowledge and preventive behavior regarding Diarrheagenic Escherichia coli infection. Method: The type of research in this study is descriptive. The research was conducted by collecting data using a Level of knowledge and preventive behavior regarding the diarrheagenic Escherichia coli infection questionnaire which will be given to respondents. Result: The results were obtained from 100 people. For the level of knowledge, there were 64 (64%) people who had good knowledge, 29 (29%) moderate people, and 7 (7%) low people. For the level of preventive behavior, 81 (81%) people of good behavior were found, 18 (18%) people were moderate and 1 (1%) were low. Conclusion: The majority of final-year medical students of Universitas Sumatera Utara are in a good category both in knowledge and preventive behavior regarding Diarrheagenic Escherichia coli. Â